Analisis Perkembangan Perusahaan Asuransi Syariah di Kota Medan pada Masa Pasca Pandemi Covid-19: Studi Kasus pada PT. Asuransi Jiwa Bumiputera Syariah Kota Medan - Hafnisyah Hafnisyah; Sri Ramadhani; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2023)
Sharia insurance is an attempt to protect and help each other between a number of people or parties through the investment of assets and tabaruk which provide a return pattern for dealing with certain risks through sharia-compliant contracts. This study aims to determine the development of the independent variable, namely the development of sharia insurance companies in Medan City and the dependent variable, namely during the post-Covid-19 pandemic (Case Study at PT. Asuransi Jiwa Bumiputera Syariah Medan City). This study uses a qualitative approach, the data used are primary data in the form of income from the Sharia Life Insurance of PT. AJS Bumiputera Medan. The results of this study indicate that the development of Islamic Insurance in Medan City during the post-Covid-19 pandemic fluctuated every year. Where in 2019-2021 there was a significant increase while in 2022 there was also a significant decrease. The factor that most influenced the rate of decline was the Covid-19 outbreak that occurred in 2019 and continued into 2021.